Kesiapan Berwirausaha Siswa SMK di Daerah Istimewa Yogyakarta - Dwi Rahdiyanta (Department of Mechanical Engineering Education, 2019)
The purpose of this study is to determine the effect of family environment factors, industry practice experience, and entrepreneurial knowledge on Vocational High Schools (VHS) students' entrepreneurship readiness in Yogyakarta. From a total population of 1095 students,300 were selected as samples using the proportional random sampling technique by means of the Krejcie and Morgan formula. The data were collected through inventories, observation sheets, and documents. The content validity was assessed through expert judgment. The construct validity was assessed using the factor analysis and the reliability using the Cronbach's Alpha formula. The data were analyzed using the descriptive analysis, regression analysis, and path analysis at a significance level of 0.05. The results show that: (1) there is a positive and significant influence of family environment, industry practice experience, and entrepreneurial knowledge on VHSs students' entrepreneurial readiness; and (2) family environment factors, industry practice experience, and entrepreneurial knowledge have a significant influence both directly and indirectly in determining the entrepreneurship readiness of VHS students.Tujuan penelitian ini adalah untuk mengetahui pengaruh faktor lingkungan keluarga, pengalaman praktik industri, dan pengetahuan kewirausahaan terhadap kesiapan berwirausaha siswa SMK di DIY. Penelitian ini merupakan penelitian korelasional yang bersifat ex-post facto. Populasi penelitian berjumlah 1095 orang siswa. Jumlah sampel penelitian pada taraf kesalahan 5% sebanyak 300 siswa ditentukan dengan formula Krejcie dan Morgan. Pengambilan sampel dilakukan dengan teknik proportional random sampling. Data dikumpulkan dengan inventori, lembar pengamatan dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang positif dan signifikan lingkungan keluarga, pengalaman praktik industri, dan pengetahuan kewirausahaan terhadap kesiapan berwirausaha siswa SMK. Disamping itu, faktor lingkungan keluarga, pengalaman praktik industri, dan pengetahuan kewirausahaan memiliki pengaruh yang signifikan baik secara langsung maupun tidak langsung dalam menentukan kesiapan berwirausaha siswa SMK